Association of gastrointestinal events with quality of life and treatment satisfaction in osteoporosis patients: results from the Medication Use Patterns, Treatment Satisfaction, and Inadequate Control of Osteoporosis Study (MUSIC OS) - Modi, A. (Osteoporos Int, 2017)
SUMMARY: The purpose of this study was to assess the association of GI events with HRQoL and treatment satisfaction. The effect of baseline GI events persisted through 1 year of follow-up, as indicated by lower EQ-5D, OPAQ-SV, and treatment satisfaction scores among patients with vs without baseline GI events. The presence of GI events is an independent predictor of decreased HRQoL and treatment satisfaction in patients being treated for osteoporosis. INTRODUCTION: The goal of this study was to assess the association of gastrointestinal (GI) events with health-related quality of life (HRQoL) and treatment satisfaction in patients being treated for osteoporosis. METHODS: MUSIC OS was a multinational, prospective, observational study examining the impact of GI events on osteoporosis management in postmenopausal women. In this analysis, HRQoL and treatment satisfaction were assessed at baseline, 6, and 12 months and compared between patients with and without GI events. Covariate-adjusted scores were calculated using multivariate least-squares regression analysis, and differences between the mean scores of patients with and without baseline and post-baseline GI events were determined. RESULTS: Among the 2959 patients in the analysis, unadjusted scores at each time point were lower (i.e., worse) for patients with GI events than patients without GI events. In adjusted analyses, the effect of baseline GI events persisted through 1 year of follow-up, as indicated by lower EQ-5D and OPAQ-SV scores at 12 months among patients with vs without baseline GI events (−0.04 for the EQ-5D utility score, −5.07 for the EQ-5D visual analog scale, −3.35 for OPAQ physical function, −4.60 for OPAQ emotional status, and −8.50 for OPAQ back pain; P ≤ 0.001 for all values). Decrements in month 12 treatment satisfaction scores were −6.46 for patients with baseline GI events and −7.88 for patients with post-baseline GI events. CONCLUSIONS: The presence of GI events is an independent predictor of decreased HRQoL and treatment satisfaction in patients being treated for osteoporosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00198-017-4116-y) contains supplementary material, which is available to authorized users.